Hubungan Ekspresi Imunohistokimia Cyclooxygenase-2 (COX-2) dengan Derajat Histopatologi Meningioma - Indri Mahrani; Delyuzar; Joko S. Lukito (Majalah Patologi Indonesia, 2019)
BackgroundMeningioma is the most common intracranial primary neoplasm in adults, which arise from arachnoid cap(meningothelial) cells. Histological appearance of a meningioma is an important predictor of tumor behavior.Cyclooxygenase-2 (COX-2) enzyme is overexpressed in different types of tumors and is known to beassociated with malignant behavior of tumors. The aim of this study was to evaluate cyclooxygenase-2 (COX-2)immunoreactivity in meningioma and to find association with histopathologic grading of meningioma.MethodsThis is an analytical descriptive study with cross sectional approach. The histopathologic grading of 22 samplesof meningioma were determined and stained with COX-2 immunohistochemistry. The color intensity: 1 (mild), 2(moderate), 3 (strong). Percentage of positive cells: 0 (0%), 1 (<10%), 2 (10-50%), 3 (>50%). The evaluationwas the sum of color intensity and percentage of positive cells: positive (>4), negative (<4).ResultsTwnty two cases of meningioma: mean age=41 years, 90.9% females, meningothelial=22.7%, grade I=77.3%).COX-2 expression: negative: 17 cases (77,3%) all was first degree of malignancy. COX-2 positive: 5 cases(22,7%): 4 cases of second degree and 1 case of third degree of malignancy. The expression of COX-2 inmeningioma cells was associated with WHO histopathologic grading (p=0.001).ConclusionThis study showed a relationship between COX-2 immunohistochemical expression and histopathologic gradingof meningioma, where COX-2 was more expressed in grades II and III.